Metal organic framework material for adsorbing and separating methane and nitrogen in wharf oil gas as well as preparation method and application of metal organic framework material

By preparing modified Al-fumarate materials, the problems of low adsorption capacity, insufficient selectivity, and poor regeneration performance in methane recovery from oil and gas at the port were solved, achieving efficient methane nitrogen separation and recovery, reducing costs, and adapting to the complex environment of the port.

CN121021845APending Publication Date: 2025-11-28DALIAN MARITIME UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511163147.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-19
Publication Date
2025-11-28

AI Technical Summary

Technical Problem

Existing adsorption methods for methane recovery from oil and gas at ports suffer from problems such as low methane adsorption capacity, insufficient selectivity, poor regeneration performance, and high adaptability and cost. They are particularly poor at low methane concentrations and are difficult to effectively separate methane from inert nitrogen gas.

Method used

A high-performance methane nitrogen adsorption and separation material was prepared by using aluminum metal nodes and fumaric acid complexed metal-organic framework (Al-fumarate) and modifying it through organic liquid post-treatment. The methane adsorption capacity and selectivity were optimized by using a simple hydrothermal process and vacuum high-temperature degassing technology.

Benefits of technology

It significantly improves the adsorption capacity and selectivity of methane, reduces regeneration energy consumption, enhances the adaptability and economy of the material, and is suitable for the recovery of complex oil and gas components at the port, supporting the construction of green ports.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121021845A_ABST
    Figure CN121021845A_ABST
Patent Text Reader

Abstract

The invention discloses a metal organic framework material for adsorbing and separating methane and nitrogen in wharf oil gas as well as a preparation method and application of the metal organic framework material. The metal organic framework material is a modified Al-fumarate material which is obtained by performing organic liquid post-treatment on a framework material formed by complexing an aluminum metal node and fumaric acid. According to the method for modifying the Al-fumarate metal organic framework material based on organic matter aftertreatment, Al-fumarate material basic powder is prepared through a simple hydrothermal process, pretreatment is performed through vacuum high-temperature degassing, then aftertreatment modification is performed through organic liquid, and the high-performance methane nitrogen adsorption and separation material is prepared. And optimization of methane adsorption capacity and methane nitrogen selectivity is realized. The material can be applied to methane adsorption and recovery in the wharf oil gas treatment process, has the technical advantages of simple preparation conditions, easily available raw materials and excellent adsorption performance, and overcomes the bottleneck of the existing material in methane adsorption.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the field of gas adsorption separation, more particularly, to a metal-organic framework material for adsorption separation of methane and nitrogen in oil and gas at a port and a preparation method and application thereof. BACKGROUND

[0002] With the continuous growth of global energy demand and the increasing prosperity of international trade, ports, as the key nodes for the transportation of oil, liquefied natural gas (LNG) and their derivatives (such as gasoline and diesel), bear an increasingly heavy loading and unloading task. In these operations, volatile organic compounds are released in large quantities in the form of oil and gas into the atmosphere, becoming a prominent environmental and resource problem. These oil and gas not only cause significant pollution to the environment, but also pose a threat to human health, while leading to the wasteful use of energy resources. Therefore, developing efficient oil and gas recovery and separation technology has become an important research direction in the field of port environmental protection and resource utilization.

[0003] Methane (CH4) as a light hydrocarbon component in oil and gas, due to its high volatility, low molecular weight (16 g / mol) and significant greenhouse effect potential (global warming potential is about 25 times that of carbon dioxide), has special importance in oil and gas recovery. Methane is widely present in the loading and unloading process of crude oil, liquefied natural gas (LNG) and light oil products, and its emission not only leads to high carbon emissions in port operations, but also leads to the waste of energy resources. Adsorption method as the mainstream technology of oil and gas recovery, its core lies in the selection and performance of adsorption materials. Developing efficient adsorption recovery materials for methane in port oil and gas is not only an urgent need for environmental protection, but also an important direction for resource recycling, which has important environmental and economic significance.

[0004] Currently, the main technologies for oil and gas recovery at the port include adsorption method, condensation method, absorption method and membrane separation method, etc. Among them, the adsorption method, due to its relatively simple equipment structure, flexible operation and lower initial investment cost, has become one of the mainstream technologies for oil and gas treatment at the port. The basic principle of adsorption method is to use porous adsorption materials (such as activated carbon, molecular sieve or silica gel) to physically adsorb oil and gas molecules, and then release them through desorption process (such as heating or reducing pressure) for recovery or further processing. In the field of methane adsorption recovery, commonly used materials include activated carbon, molecular sieve and silica gel, etc. These materials, due to their high specific surface area and pore structure, show certain advantages in VOCs capture; however, for the recovery of methane, a light hydrocarbon, the existing adsorption technology faces significant challenges.

[0005] Activated carbon is the most widely used adsorption material, with a specific surface area usually ranging from 500 to 1500 m 2With a high porosity, activated carbon adsorbs methane via van der Waals forces, demonstrating excellent performance in VOCs recovery from oil and gas. However, the high nitrogen content in oil and gas due to inerting results in significantly reduced methane adsorption capacity compared to propane and butane. Molecular sieves, with their regular pore size (0.4–1.0 nm) and tunable surface chemistry, are also commonly used for methane separation. However, the strong polarity of molecular sieve surfaces also leads to strong nitrogen adsorption, and they are susceptible to competitive adsorption by water vapor, resulting in poor methane separation performance in oil and gas. Silica gel, as a hydrophilic adsorbent, is primarily used to capture polar VOCs, exhibiting weak adsorption capacity for non-polar methane and performing poorly in the high-humidity environment of a port.

[0006] Although adsorption has certain advantages in oil and gas recovery, existing technologies have the following significant problems in the specific scenario of methane recovery in port oil and gas: (1) Low methane adsorption capacity. The non-polarity, small molecular size and low heat of adsorption of methane (usually <20kJ / mol) make it difficult for traditional materials to effectively capture it, especially under low concentration conditions at the port (methane content <20%), resulting in a larger device size. (2) Insufficient selectivity, especially for inert gas nitrogen. The separation selectivity of methane and nitrogen is usually less than 4. This lack of selectivity not only increases the complexity of subsequent processing, but also reduces the economic value of methane recovery. At the same time, port oil and gas is a multi-component mixture containing various hydrocarbons such as methane, ethane, propane and aromatics. The competitive adsorption of polar molecules greatly reduces its selectivity. (3) Poor regeneration performance. The interference of polar molecules requires high regeneration temperature for active sites. In particular, the regeneration temperature after molecular sieve adsorbs water molecules is as high as 200℃, and the energy consumption is about 1-2MJ / kg. (4) Adaptability and cost issues: The composition of oil and gas at the terminal fluctuates greatly (e.g., methane content >90% during LNG loading and unloading, and <15% during crude oil loading and unloading). Traditional materials are difficult to adapt to such changes due to their low selectivity for methane and nitrogen.

[0007] To address the challenges of methane recovery, particularly the separation of methane from inert gases, several improved solutions have been proposed in recent years to overcome these technical bottlenecks. Researchers have explored the use of nanoscale adsorption materials, such as metal-organic frameworks (MOFs), carbon nanotubes (CNTs), modified activated carbon, and composite materials, to enhance the adsorption capacity and selectivity of methane. While these improvements have shown promise in laboratory settings or small-scale experiments, they still face challenges related to cost, stability, and practicality in real-world port environments.

[0008] Against this backdrop, developing a highly efficient material for the adsorption and recovery of methane from oil and gas at port is of great significance. Summary of the Invention

[0009] The purpose of this invention is to overcome the aforementioned deficiencies in existing technologies and provide a metal-organic framework (MOF) material for methane and nitrogen adsorption and separation in port oil and gas processes, which has readily available raw materials and a simple and easy-to-implement modification process. This invention relates to a method for modifying Al-fumarate MOF materials based on organic post-processing. Al-fumarate base powder is prepared through a simple hydrothermal process, pretreated by vacuum high-temperature degassing, and then post-treated with an organic liquid to prepare a high-performance methane and nitrogen adsorption and separation material, optimizing methane adsorption capacity and methane-nitrogen selectivity. This material can be applied to methane adsorption and recovery in port oil and gas processing, possessing the technical advantages of simple preparation conditions, readily available raw materials, and excellent adsorption performance, overcoming the bottlenecks of existing materials in methane adsorption.

[0010] The technical objectives of this invention are: first, to significantly improve the adsorption capacity and selectivity of methane to meet the recovery needs of complex oil and gas components at ports; second, to enhance the regeneration performance of materials to adapt to high humidity and continuous operating environments; third, to reduce material costs and preparation difficulty to promote industrial applications; and fourth, to achieve efficient recovery and resource utilization of methane to support the construction of green ports. The invention particularly focuses on the research and development of methane adsorption and recovery materials, aiming to improve methane capture efficiency and recovery value through innovative material design.

[0011] To achieve the above objectives, the technical solution of the present invention is as follows:

[0012] A method for preparing a metal-organic framework material for the adsorption and separation of methane and nitrogen in port oil and gas, wherein the metal-organic framework material is a modified Al-fumarate material obtained by post-treatment with an organic liquid after the framework material composed of aluminum metal nodes and fumaric acid complexes.

[0013] Optionally, the modified Al-fumarate material can be prepared as follows:

[0014] S1. Dissolve and disperse the aluminum salt in water to obtain mixture A;

[0015] S2. Dissolve and disperse sodium fumarate in water and heat to obtain mixture B;

[0016] S3. Add the mixture A dropwise to the mixture B and stir until the mixture is homogeneous to obtain mixture C;

[0017] S4. The mixture C is subjected to a crystallization reaction. After the reaction is completed, the precipitate is separated by filtration, washed with deionized water until neutral, and dried to obtain Al-fumarate basic powder.

[0018] S5. The Al-fumarate base powder is vacuum dried, and then cooled to room temperature under vacuum conditions to obtain active powder D.

[0019] S6. The active powder D and the organic liquid are mixed and then post-processed. The solid product is then separated by filtration and vacuum dried to obtain the modified Al-fumarate material.

[0020] Optionally, in step S1, Al in the mixture A 3+ The molar ratio with water is 0.01 to 1.

[0021] Optionally, in step S1, the aluminum salt includes at least one of aluminum chloride, aluminum acetate, aluminum nitrate, and aluminum sulfate; preferably, aluminum nitrate and / or aluminum sulfate are used as raw materials.

[0022] Optionally, in step S2, the heating temperature is 35–95°C.

[0023] Optionally, in step S2, the concentration of the mixture B is 0.01 to 0.2 mol / L.

[0024] Optionally, in step S3, the mixture A and the mixture B are prepared according to Al. 3+ The mixture is prepared in a molar ratio of 1 to 2:1 with sodium fumarate. Specifically, due to the low price and easy availability of the raw materials, those skilled in the art can adjust the Al mixture according to the actual situation. 3+ Adjust the molar ratio with sodium fumarate.

[0025] Optionally, in step S4, the temperature of the crystallization reaction is 50–180°C; preferably, the temperature of the crystallization reaction is 50–130°C.

[0026] Optionally, in step S4, the crystallization reaction takes 2 to 24 hours; preferably, the crystallization reaction takes 2 to 12 hours.

[0027] Optionally, the modification method employed in this invention has good applicability to the sources of Al-fumarate base powders. It can be synthesized using either a high-temperature, high-pressure hydrothermal process or a low-temperature, ambient-pressure process. Those skilled in the art can choose the preparation method of the Al-fumarate base powder based on their own production and raw material characteristics. Considering the mildness and safety of the synthesis process, this invention preferentially recommends the synthesis of Al-fumarate base powders at low temperature and ambient pressure, with a preferred crystallization temperature of 50–100°C, and particularly a preferred crystallization temperature of 50–80°C. Therefore, the use of green energy sources such as solar thermal energy can be considered to provide heat.

[0028] Optionally, in step S4, the drying temperature is 80–120°C, and the drying time is 2–6 hours.

[0029] Optionally, in step S4, the specific surface area of ​​the Al-fumarate base powder is 900–1000 m². 2 With a surface area of ​​ / g, it is an excellent porous adsorbent material.

[0030] Optionally, in step S5, the vacuum drying temperature is 100–150°C, and the vacuum drying time is 2–24 hours.

[0031] Optionally, in step S6, the organic liquid includes at least one of N,N-dimethylformamide, acetonitrile, methanol, ethanol, nitromethane, pyridine, 1,4-dioxane, ethyl acetate, methyl acetate, dichloromethane, diethyl ether, toluene, xylene, cyclohexane, n-hexane, n-heptane, n-octane, isooctane, dimethylacetamide, cyclopentanone, cyclohexanone, propyl acetate, butyl acetate, methyl formate, ethyl formate, dimethyl ether, methylcyclohexane, ethylbenzene, chlorobenzene, dichlorobenzene, n-butanol, and isobutanol.

[0032] Optionally, one of the most significant highlights of this invention is the use of organic liquids for the post-treatment modification of Al-fumarate materials, resulting in excellent methane-nitrogen separation performance. The organic liquids used are primarily selected from organic compounds with a dielectric constant of 2–60. Factors such as viscosity, molecular size, and price of the organic liquids must also be considered. Therefore, this invention recommends organic compounds that are inexpensive, have low toxicity, low viscosity, and small molecular size. Considering these factors, preferably, the organic liquid includes at least one of methanol, ethanol, acetonitrile, toluene, xylene, cyclopentanone, cyclohexanone, cyclohexane, pyridine, N,N-dimethylformamide, ethyl acetate, methyl acetate, ethyl formate, and methyl formate. More preferably, the organic liquid includes at least one of methanol, ethanol, acetonitrile, cyclohexane, pyridine, N,N-dimethylformamide, ethyl acetate, and methyl formate. Even more preferably, to facilitate the recovery of the post-treatment organic liquid, this invention preferentially recommends the use of a single organic liquid.

[0033] Optionally, in step S6, the mass ratio of the organic liquid to the active powder D is 1.5 to 9:1; preferably, considering both modification efficiency and cost, the mass ratio of the organic liquid to the active powder D is 3 to 6:1.

[0034] Optionally, in step S6, the post-treatment temperature is 0–60°C. Preferably, the post-treatment temperature is also an effective means of controlling the performance of modified Al-fumarate materials. Those skilled in the art can select the post-treatment temperature based on the polarity, viscosity, volatility, and other properties of the organic liquid. Considering the post-treatment cost, this invention preferentially recommends a post-treatment temperature of 20–45°C. However, for some organic liquids, the temperature needs to be lowered, and for organic liquids with high viscosity, the temperature needs to be increased.

[0035] Optionally, in step S6, the post-treatment time is 4–48 hours. Those skilled in the art can adjust the required post-treatment time within 4–48 hours as needed to control the methane adsorption and separation performance of the modified Al-fumarate material. Preferably, the post-treatment time is 10–24 hours.

[0036] Optionally, in step S6, the vacuum drying temperature is 30–80°C, and the vacuum drying time is 0.5–24 h; preferably, the vacuum drying temperature is 55–65°C. Specifically, those skilled in the art can adjust the drying temperature according to the boiling point and volatility of the organic liquid. For organic liquids with high boiling points, the drying temperature can be appropriately increased, while for organic compounds with low boiling points, such as methyl formate, drying can be carried out at room temperature.

[0037] Optionally, in step S6, the amount of organic liquid retained in the modified Al-fumarate material is <10%, preferably <5%. The lower the amount of organic liquid retained, the better the permeability of the Al-fumarate framework can be maintained, and the surface polarity of the Al-fumarate material can be reduced, which is beneficial to improving the adsorption capacity and selectivity of the modified Al-fumarate.

[0038] Optionally, the specific surface area of ​​the modified Al-fumarate material is 200–950 m². 2 / g, the surface area of ​​the modified material shows a decreasing trend; in order to provide more adsorption sites, a specific surface area of ​​300-850m² is preferred. 2 The modified material with a specific surface area of ​​450–800 m² / g is preferred. 2 / g of modified materials.

[0039] The present invention also discloses a metal-organic framework material for methane adsorption and separation in port oil and gas, prepared by the above-described method. The framework structure of the metal-organic framework material is a monoclinic crystal belonging to the P21 / C space group, with cell parameters of a = 6.8419, b = 12.0877, c = 14.2070, α = 90.0, β = 122.5, γ = 90.0; it has a one-dimensional pore structure with a pore size of 0.6 nm × 0.45 nm.

[0040] Optionally, the present invention can effectively change the pore structure and properties by supporting organic matter, increase the proportion of organic matter per unit skeleton volume, reduce the surface charge gradient, and have better hydrophobic properties, thereby improving the affinity of methane and weakening the adsorption of nitrogen, thus achieving efficient adsorption, separation and recovery of methane and nitrogen.

[0041] The present invention also discloses the application of a metal-organic framework material prepared by the above preparation method for the adsorption and separation of methane in port oil and gas, wherein the metal-organic framework material is used for the adsorption, separation and recovery of methane and nitrogen in port oil and gas.

[0042] Optionally, the metal-organic framework material has a methane adsorption capacity of 0.65–1.8 mmol / g at 298 K and 1 bar. The methane adsorption capacity of the post-treated Al-fumarate material exhibits both increases and decreases, but remains generally greater than 0.5 mmol / g, meeting the requirements of the adsorption separation process. However, considering that a large adsorption capacity helps reduce the volume of the adsorption device, a value of 0.8–1.5 mmol / g is preferred, more preferably 1.0–1.5 mmol / g, and most preferably 1.2–1.5 mmol / g is ideal. At 298 K and 1 bar, the methane-nitrogen separation selectivity is 5–10. The methane-nitrogen separation selectivity of the post-treated Al-fumarate material significantly increases to above 5, fully meeting the requirements of industrial adsorption separation processes. However, considering that high adsorption selectivity helps improve the purity and efficiency of methane recovery and enhances the equipment's compatibility with high- and low-concentration methane separation scenarios, making it suitable for methane separation processes in port oil and gas recovery, a value of 6–10 is preferred, more preferably 8–10, demonstrating good adsorption capacity.

[0043] The modified Al-fumarate material of this invention is suitable for the separation of methane and nitrogen, and is particularly suitable for methane recovery processes in port oil and gas. The organic liquid-modified material not only enhances the methane adsorption capacity and the selectivity of methane-nitrogen separation, but also reduces the surface polarity of the adsorbent material, thereby reducing the regeneration energy consumption. Importantly, port oil and gas is complex, containing various organic compounds; the introduction of organic liquids into the Al-fumarate material may help enhance the material's adsorption and separation performance, significantly improving the material's adaptability to oil and gas.

[0044] Implementing the embodiments of the present invention will have the following beneficial effects:

[0045] 1. The modified Al-fumarate material can achieve a methane adsorption capacity of 1.8 mmol / g at room temperature and pressure, which is better than most reported methane adsorption materials and is 70% higher than that of Al-fumarate base material.

[0046] 2. The methane-nitrogen separation selectivity of the modified Al-fumarate material at room temperature and pressure can reach 10, which is better than most reported methane adsorption materials, 2.2 times that of Al-fumarate basic materials, and 2 to 3 times that of commercial activated carbon materials.

[0047] 3. The entire process of preparing modified Al-fumarate materials can be carried out under mild conditions. In particular, the modification process is extremely simple and has a large production capacity, which has significant technical and economic advantages.

[0048] 4. The modified Al-fumarate material prepared by the method of the present invention not only helps to reduce greenhouse gas emissions, but also enhances the resource utilization value of methane, providing a new technical path for environmental protection and sustainable development. Attached Figure Description

[0049] Figure 1 The isothermal adsorption curve diagram of the material prepared in Example 1 of the present invention was measured at 298K and 1 bar.

[0050] Figure 2 The isothermal adsorption curve diagram of the material prepared in Example 2 of the present invention was measured at 298K and 1 bar.

[0051] Figure 3 The isothermal adsorption curve diagram of the material prepared in Example 3 of the present invention was measured at 298K and 1 bar.

[0052] Figure 4 The isothermal adsorption curve diagram of the material prepared in Example 4 of the present invention was measured at 298K and 1 bar.

[0053] Figure 5 The isothermal adsorption curve diagram of the material prepared in Example 5 of the present invention was measured at 298K and 1 bar.

[0054] Figure 6 The isothermal adsorption curve diagram of the material prepared in Example 6 of the present invention was measured at 298K and 1 bar.

[0055] Figure 7 The isothermal adsorption curve diagram of the material prepared in Example 7 of the present invention was measured at 298K and 1 bar.

[0056] Figure 8 The isothermal adsorption curve diagram of the material prepared in Example 8 of the present invention was measured at 298K and 1 bar.

[0057] Figure 9 The isothermal adsorption curve diagram of the material prepared in Example 9 of the present invention was measured at 298K and 1 bar. Detailed Implementation

[0058] The present invention will be further described below with reference to specific embodiments, but these embodiments do not limit the invention in any way. Unless otherwise specified, all raw materials used in the embodiments are commercially available products.

[0059] The analytical and testing methods used in Examples 1-9 include:

[0060] 1. Specific Surface Area and Pore Structure Characterization: Based on the principle of physical adsorption, the specific surface area and pore structure parameters of the adsorbent material were calculated using Ar adsorption isotherms at 97 K. Before testing, the samples were pretreated in a high-vacuum environment at 100℃ for at least 2 hours, with the adsorption pressure range set to 0–760 mmHg.

[0061] 2. Static adsorption performance test: CH4 and N2 were used as probe gases, and their adsorption isotherms were measured at 298 K. The adsorption pressure range was 0–1 bar, and the separation selectivity was calculated using the LF adsorption isotherm model. The sample pretreatment conditions were activation in a high vacuum environment at 80–100 °C for more than 2 hours.

[0062] Example 1

[0063] (1) Preparation of Al-fumarate active powder:

[0064] 18.5 g of aluminum sulfate octahydrate (Al2(SO4)3·18H2O) was dissolved in 300 mL of deionized water to prepare mixture A. 8.9 g of sodium fumarate was dissolved in 200 mL of deionized water and heated to 80 °C to form mixture B. Mixture A was slowly added dropwise to mixture B under magnetic stirring (500 r / min) and constant temperature of 80 °C. The resulting mixture C was then crystallized at 80 °C for 2 h under stirring conditions. After the reaction, the mixture was vacuum filtered, washed with deionized water until neutral, and the filter cake was dried at 100 °C for 4 h to obtain Al-fumarate basic powder. Subsequently, the Al-fumarate basic powder was activated in a vacuum environment at 120 °C for 2 h and cooled to room temperature to obtain active powder D.

[0065] (2) Post-processing:

[0066] 10g of active powder D, 20g of acetonitrile, and 20g of cyclohexane were added to a round-bottom flask and placed in a constant-temperature magnetic stirrer. The mixture was stirred continuously at 130r / min for 24h at 45℃. The reaction solution was kept sealed to prevent solvent evaporation. After post-treatment, the solid product was separated by vacuum filtration through a Buchner funnel. The filter cake was transferred to a vacuum drying oven and dried at 60℃ for 6h to finally obtain the modified Al-fumarate material S1#.

[0067] The specific surface area of ​​the obtained modified Al-fumarate material S1# is 810 m². 2 / g, the methane adsorption capacity at room temperature and pressure is 1.41 mmol / g.

[0068] The performance evaluation results of the obtained adsorbent are as follows: Figure 1 As shown, the calculated methane nitrogen adsorption selectivity is 9.22.

[0069] Example 2

[0070] (1) Preparation of Al-fumarate active powder:

[0071] 14.2 g of aluminum sulfate octahydrate (Al2(SO4)3·18H2O) and 5.8 g of aluminum nitrate (Al(NO3)3·9H2O) were dissolved in 350 mL of deionized water to prepare mixture A. 7.5 g of sodium fumarate was dissolved in 150 mL of deionized water at room temperature to form mixture B. Mixture A was slowly added dropwise to mixture B under stirring at room temperature. The resulting mixture C was then transferred to a polytetrafluoroethylene-lined high-pressure reactor and crystallized at 130 °C for 24 h. After the reaction, the mixture was vacuum filtered, washed with deionized water until neutral, and the filter cake was dried at 100 °C for 4 h to obtain Al-fumarate basic powder. The Al-fumarate basic powder was then activated in a vacuum environment at 120 °C for 2 h and cooled to room temperature to obtain active powder D.

[0072] (2) Post-processing:

[0073] 12g of active powder D, 10g of methyl formate, 10g of formic acid and 20g of cyclohexane were added to a reaction vessel and stirred and refluxed at 100r / min for 20h at a constant temperature of 35℃. After post-treatment, the solid product was separated by vacuum filtration and the filter cake was dried under vacuum at 60℃ for 6h to finally obtain the modified Al-fumarate material S2#.

[0074] The specific surface area of ​​the obtained modified Al-fumarate material S2# is 650 m². 2 / g, the methane adsorption capacity at room temperature and pressure is 1.49 mmol / g.

[0075] The performance evaluation results of the obtained adsorbent are as follows: Figure 2 As shown, the calculated methane nitrogen adsorption selectivity is 9.6.

[0076] Example 3

[0077] (1) Preparation of Al-fumarate active powder:

[0078] 9.7 g of aluminum sulfate octahydrate (Al2(SO4)3·18H2O) and 15.2 g of aluminum nitrate (Al(NO3)3·9H2O) were dissolved in 300 mL of deionized water to prepare mixture A. 10.2 g of sodium fumarate was dissolved in 200 mL of deionized water and heated to 85 °C to form mixture B. Mixture A was slowly added dropwise to mixture B under stirring. The resulting mixture C was then transferred to a polytetrafluoroethylene-lined high-pressure reactor and crystallized at 160 °C for 8 h. After the reaction, the mixture was vacuum filtered, washed with deionized water until neutral, and the filter cake was dried at 100 °C for 4 h to obtain Al-fumarate basic powder. The Al-fumarate basic powder was then activated in a vacuum environment at 120 °C for 2 h and cooled to room temperature to obtain active powder D.

[0079] (2) Post-processing:

[0080] 10g of active powder D, 30g of DMF and ethanol were added to a reaction vessel and stirred at 130r / min for 18h at a constant temperature of 40℃. After post-treatment, the solid product was separated by vacuum filtration and the filter cake was dried under vacuum at 60℃ for 6h to finally obtain the modified Al-fumarate material S3#.

[0081] The specific surface area of ​​the obtained modified Al-fumarate material S3# is 650 m². 2 / g, with a methane adsorption capacity of 0.76 mmol / g at room temperature and pressure.

[0082] The performance evaluation results of the obtained adsorbent are as follows: Figure 3 As shown, the calculated methane nitrogen adsorption selectivity is 5.6.

[0083] Example 4

[0084] (1) Preparation of Al-fumarate active powder:

[0085] 27.1 g of aluminum nitrate (Al(NO3)3·9H2O) was dissolved in 450 mL of deionized water to prepare mixture A. 9.8 g of sodium fumarate was dissolved in 200 mL of deionized water and heated to 70 °C to form mixture B. Mixture A was slowly added dropwise to mixture B under stirring. The resulting mixture C was then transferred to a polytetrafluoroethylene-lined high-pressure reactor and crystallized at 150 °C for 12 h. After the reaction, the mixture was vacuum filtered, washed with deionized water until neutral, and the filter cake was dried at 100 °C for 4 h to obtain Al-fumarate base powder. The Al-fumarate base powder was then activated in a vacuum environment at 120 °C for 2 h and cooled to room temperature to obtain active powder D.

[0086] (2) Post-processing:

[0087] 15g of active powder D, 25g of ethyl acetate, and 15g of formic acid were added to a reaction vessel and stirred at 130r / min for 30h at a constant temperature of 35℃. After post-treatment, the solid product was separated by vacuum filtration, and the filter cake was dried under vacuum at 60℃ for 6h to finally obtain the modified Al-fumarate material S4#.

[0088] The specific surface area of ​​the obtained modified Al-fumarate material S4# is 566 m². 2 / g, the methane adsorption capacity at room temperature and pressure is 1.39 mmol / g.

[0089] The performance evaluation results of the obtained adsorbent are as follows: Figure 4 As shown, the calculated methane nitrogen adsorption selectivity is 7.5.

[0090] Example 5

[0091] (1) Preparation of Al-fumarate active powder:

[0092] 30.6 g of aluminum nitrate (Al(NO3)3·9H2O) was dissolved in 400 mL of deionized water to prepare mixture A. 11.5 g of sodium fumarate was dissolved in 220 mL of deionized water at 50 °C to prepare mixture B. Mixture A was slowly added to mixture B under stirring at 50 °C. The resulting mixture C was then transferred to a polytetrafluoroethylene-lined high-pressure reactor and crystallized at 120 °C for 24 h. After the reaction, the mixture was vacuum filtered, washed with deionized water until neutral, and the filter cake was dried at 100 °C for 4 h to obtain Al-fumarate base powder. The Al-fumarate base powder was then activated in a vacuum environment at 120 °C for 2 h and cooled to room temperature to obtain active powder D.

[0093] (2) Post-processing:

[0094] 18g of active powder D, 30g of cyclohexane, and 20g of formic acid were added to a reaction vessel and stirred at 130r / min for 28h at a constant temperature of 50℃. After post-treatment, the solid product was separated by vacuum filtration, and the filter cake was dried under vacuum at 60℃ for 6h to finally obtain the modified Al-fumarate material S5#.

[0095] The specific surface area of ​​the obtained modified Al-fumarate material S5# is 487 m². 2 / g, the methane adsorption capacity at room temperature and pressure is 1.16 mmol / g.

[0096] The performance evaluation results of the obtained adsorbent are as follows: Figure 5 As shown, the calculated methane nitrogen adsorption selectivity is 6.6.

[0097] Example 6

[0098] (1) Preparation of Al-fumarate active powder:

[0099] 8.2 g of aluminum sulfate (Al2(SO4)3·18H2O), 11.7 g of aluminum trichloride (AlCl3·6H2O), and 7.9 g of aluminum nitrate (Al(NO3)3·9H2O) were mixed and dissolved in 380 mL of deionized water to prepare mixture A. 12.3 g of sodium fumarate was dissolved in 240 mL of deionized water at 40 °C to form mixture B. Mixture A was slowly added dropwise to mixture B under stirring at 40 °C. The resulting mixture C was then transferred to a polytetrafluoroethylene-lined high-pressure reactor and crystallized at 130 °C for 20 h. After the reaction, the mixture was vacuum filtered, washed with deionized water until neutral, and the filter cake was dried at 100 °C for 4 h to obtain Al-fumarate basic powder. The Al-fumarate basic powder was then activated in a vacuum environment at 120 °C for 2 h and cooled to room temperature to obtain active powder D.

[0100] (2) Post-processing:

[0101] 10g of active powder D and 40g of DMF were added to a reaction vessel and stirred at 400r / min for 26h at a constant temperature of 55℃. After post-treatment, the solid product was separated by vacuum filtration and the filter cake was dried at 30℃ for 12h to finally obtain the modified Al-fumarate material S6#.

[0102] The specific surface area of ​​the obtained modified Al-fumarate material S6# is 397 m². 2 / g, with a methane adsorption capacity of 0.75 mmol / g at room temperature and pressure.

[0103] The performance evaluation results of the obtained adsorbent are as follows: Figure 6 As shown, the calculated methane nitrogen adsorption selectivity is 5.5.

[0104] Example 7

[0105] (1) Preparation of Al-fumarate active powder:

[0106] 20.3 g of aluminum sulfate (Al2(SO4)3·18H2O) and 5.8 g of aluminum trichloride (AlCl3·6H2O) were mixed and dissolved in 360 mL of deionized water to prepare mixture A. 9.6 g of sodium fumarate was dissolved in 180 mL of deionized water and heated to 80 °C to form mixture B. Mixture A was slowly added dropwise to mixture B under vigorous stirring. The resulting mixture C was then transferred to a polytetrafluoroethylene-lined high-pressure reactor and crystallized at 120 °C for 24 h. After the reaction, the mixture was vacuum filtered, washed with deionized water until neutral, and the filter cake was dried at 100 °C for 4 h to obtain Al-fumarate basic powder. The Al-fumarate basic powder was then activated in a vacuum environment at 120 °C for 2 h and cooled to room temperature to obtain active powder D.

[0107] (2) Post-processing:

[0108] 10g of active powder D, 20g of methanol and 20g of DMF were added to a reaction vessel and stirred at 130r / min for 22h at a constant temperature of 45℃. After post-treatment, the solid product was separated by vacuum filtration and the filter cake was dried under vacuum at 60℃ for 6h to finally obtain the modified Al-fumarate material S7#.

[0109] The specific surface area of ​​the obtained modified Al-fumarate material S7# is 425 m². 2 / g, the methane adsorption capacity at room temperature and pressure is 1.05 mmol / g.

[0110] The performance evaluation results of the obtained adsorbent are as follows: Figure 7 As shown, the calculated methane nitrogen adsorption selectivity is 5.6.

[0111] Comparative Example 1

[0112] 2.24 g of fumaric acid and 4.21 g of AlCl3·6H2O were dissolved in 100 mL of DMF. After thorough stirring, the solution was poured into a polytetrafluoroethylene-lined reactor and reacted at 130 °C for 24 h. The resulting precipitate was washed with acetone and methanol and then dried in a vacuum drying oven at 160 °C for 12 h to obtain a single-ligand metal-organic framework powder, labeled MOF-1-Fu. Adsorption performance tests were performed on the above sample. Before the adsorption tests, the sample was subjected to a high vacuum (<10) at 140 °C. -6 Activation was performed for 6 hours under the given conditions (Pa). The specific surface area was calculated from the Ar adsorption isotherm at 87 K, and was found to be 983 m². 2 / g. The performance evaluation results of the obtained adsorbent are as follows: Figure 8 As shown, the adsorption capacity of methane was measured to be 1.08 mmol / g and the adsorption capacity of N2 was 0.34 mmol / g at 298 K and 1 bar. The calculated Henry adsorption selectivity of CH4 / N2 was 4.1.

[0113] Comparative Example 2

[0114] Aluminum sulfate octahydrate (0.4 g, 0.6 mmol), sodium hydroxide (0.15 g, 3.6 mmol), and fumaric acid (0.14 g, 1.2 mmol) were dissolved in water (10 mL) and sonicated for 5 minutes. The mixture was then heated at 363 K for 2 hours. The product was collected by filtration and washed with water. Adsorption performance tests were performed on the above samples. Before the adsorption tests, the samples were subjected to a high vacuum (<10 °C) at 140 °C. -6 Activation was performed for 6 hours under the given conditions (Pa). The specific surface area was calculated from the Ar adsorption isotherm at 87 K, and was found to be 937 m². 2 / g. The performance evaluation results of the obtained adsorbent are as follows: Figure 9 As shown, the adsorption capacity of methane was measured to be 1.01 mmol / g and the adsorption capacity of N2 was 0.33 mmol / g at 298 K and 1 bar. The calculated Henry adsorption selectivity of CH4 / N2 was 3.9.

[0115] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are specific and detailed, they should not be construed as limiting the scope of the patent application. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the scope of protection of the present invention. Therefore, the scope of protection of this patent should be determined by the appended claims.

Claims

1. A method for preparing a metal-organic framework material for the adsorption and separation of methane and nitrogen in port oil and gas, characterized in that, The metal-organic framework material is a modified Al-fumarate material obtained by post-treatment with an organic liquid after the framework material composed of aluminum metal nodes and fumaric acid complexes are formed.

2. The preparation method according to claim 1, characterized in that, The preparation method of the modified Al-fumarate material is as follows: S1. Dissolve and disperse the aluminum salt in water to obtain mixture A; S2. Dissolve and disperse sodium fumarate in water and heat to obtain mixture B; S3. Add the mixture A dropwise to the mixture B and stir until the mixture is homogeneous to obtain mixture C; S4. The mixture C is subjected to a crystallization reaction. After the reaction is completed, the precipitate is separated by filtration, washed with deionized water until neutral, and dried to obtain Al-fumarate basic powder. S5. The Al-fumarate base powder is vacuum dried, and then cooled to room temperature under vacuum conditions to obtain active powder D. S6. The active powder D and the organic liquid are mixed and then post-processed. The solid product is then separated by filtration and vacuum dried to obtain the modified Al-fumarate material.

3. The preparation method according to claim 2, characterized in that, In step S1, Al in the mixture A 3+ The molar ratio with water is 0.01 to 1; The aluminum salt includes at least one of aluminum chloride, aluminum acetate, aluminum nitrate, and aluminum sulfate.

4. The preparation method according to claim 2, characterized in that, In step S2, the heating temperature is 35–95°C; The concentration of the mixture B is 0.01–0.2 mol / L.

5. The preparation method according to claim 2, characterized in that, In step S3, the mixture A and the mixture B are processed according to Al. 3+ Mix with sodium fumarate at a molar ratio of 1 to 2:1; In step S5, the vacuum drying temperature is 100-150°C, and the vacuum drying time is 2-24 hours.

6. The preparation method according to claim 2, characterized in that, In step S4, the temperature of the crystallization reaction is 50–180°C, and the time of the crystallization reaction is 2–24 hours. The drying temperature is 80–120°C, and the drying time is 2–6 hours. The specific surface area of ​​the Al-fumarate base powder is 900-1000 m². 2 / g.

7. The preparation method according to claim 2, characterized in that, In step S6, the organic liquid includes at least one of N,N-dimethylformamide, pyridine, acetonitrile, methanol, ethanol, nitromethane, 1,4-dioxane, ethyl acetate, methyl acetate, dichloromethane, diethyl ether, toluene, xylene, cyclohexane, n-hexane, n-heptane, n-octane, isooctane, dimethylacetamide, cyclopentanone, cyclohexanone, propyl acetate, butyl acetate, methyl formate, ethyl formate, dimethyl ether, methylcyclohexane, ethylbenzene, chlorobenzene, dichlorobenzene, n-butanol, and isobutanol. The mass ratio of the organic liquid to the active powder D is 1.5 to 9:1; The post-treatment temperature is 0–60°C, and the post-treatment time is 4–48 hours. The vacuum drying temperature is 30–80°C, and the vacuum drying time is 0.5–24 h. The amount of organic liquid retained in the modified Al-fumarate material is <10%; The modified Al-fumarate material has a specific surface area of ​​200–950 m². 2 / g.

8. A metal-organic framework material for methane adsorption and separation in port oil and gas, prepared by the method according to any one of claims 1-7, characterized in that, The framework structure of the metal-organic framework material is a monoclinic crystal with a one-dimensional porous structure.

9. The application of a metal-organic framework material prepared by the preparation method according to any one of claims 1-7 for the adsorption and separation of methane in port oil and gas, characterized in that, The metal-organic framework material is used for the adsorption, separation, and recovery of methane nitrogen in port oil and gas.

10. The application according to claim 9, characterized in that, The metal-organic framework material exhibits a methane adsorption capacity of 0.65–1.8 mmol / g and a methane-nitrogen separation selectivity of 5–10 under conditions of 298 K and 1 bar.